1996
DOI: 10.1128/aem.62.6.2081-2085.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR, nested PCR, and fluorescent antibodies for detection of Giardia and Cryptosporidium species in wastewater

Abstract: Giardiasis and cryptosporidiosis are diseases caused by the protozoan parasites Giardia lamblia and Cryptosporidium parvum. Waterborne transmission of these organisms has become more prevalent in recent years, and regulatory agencies are urging that source and finished water be screened for these organisms. A major problem associated with testing for these organisms is the lack of reliable methodologies and baseline information on the prevalence of these parasites in various water sources. Our study addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(34 citation statements)
references
References 24 publications
0
32
0
2
Order By: Relevance
“…Our results demonstrate the effectiveness of IMS in eliminating PCR inhibitors. Mayer and Palmer (1996) used IFA and nested PCR to evaluate the presence of cryptosporidial oocysts in sewage ef¯uent and reported a 70% agreement between the results from both methods. Chung et al (1998) showed there to be an 84% correlation between PCR and IFA in spiked municipal drinking water samples and a correlation of up to 97Á2% between nested PCR and IFA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate the effectiveness of IMS in eliminating PCR inhibitors. Mayer and Palmer (1996) used IFA and nested PCR to evaluate the presence of cryptosporidial oocysts in sewage ef¯uent and reported a 70% agreement between the results from both methods. Chung et al (1998) showed there to be an 84% correlation between PCR and IFA in spiked municipal drinking water samples and a correlation of up to 97Á2% between nested PCR and IFA.…”
Section: Discussionmentioning
confidence: 99%
“…Stinear et al (1996) developed a reverse transcription (RT)-peR based on the detection of mRNA from a C. parvum heat shock protein (hsp) that was capable of detecting a single viable oocyst from concentrated samples in a rapid (I-day) assay. Mayer and Palmer (1996) compared PCR, nested PCR, and fluorescent antibodies (IFA) for the detection of Cryptosporidium and Giardia in wastewater samples. They found a good correlation between the IFA and PCR detection methods and concluded that PCR may be a useful tool in the analysis of environmental samples for these organisms.…”
Section: Protozoamentioning
confidence: 99%
“…Molecular methods such as PCR have been proposed as an alternative to IFA for the detection of C. parvum in environmental samples (Mayer and Palmer 1996;Kaucner and Stinear 1998). The results of this study indicate that the cell wall antigenic components are more susceptible to microbial activity than the genome.…”
Section: Discussionmentioning
confidence: 88%
“…These results suggest that although the cell wall was digested, it protected the oocysts' DNA from extracellular nucleases. Mayer and Palmer (1996) compared the detection sensitivity of C. parvum oocysts from wastewater by IFA and PCR (Mayer and Palmer 1996). The presence of humic substances resulted in an inhibition of DNA synthesis by PCR.…”
Section: Discussionmentioning
confidence: 99%